Effects of atmospheric aging processes on carbonaceous species and water-soluble inorganic ions in biomass burning aerosols. (1st November 2022) - Guo, Xiao; Wang, Xiaoqing; Dai, Wenting; Ho, Kin Fai; Liu, Suixin; Wang, Qiyuan; Shen, Minxia; Liu, Yali; Zhang, Yifan; Cao, Yue; Qi, Weining; Li, Lu; et al.
Abstract: Biomass burning (BB) has been considered as a major source for primary aerosols and gas pollutants in the atmosphere, but the influence of atmospheric aging processes on the chemical compositions of BB aerosols remains unclear. In this study, a combustion chamber and an oxidation flow reactor were combined to simulate fresh and 7-day aged PM2.5 from burning of rice, maize, and wheat straws in a laboratory. The emission factors (EFs) of PM2.5 mass, carbonaceous species ( i.e . organic carbon (OC) and elemental carbon (EC)), and water-soluble inorganic ions in both fresh and 7-day aged samples were determined. The EFs of PM2.5, OC, EC, and ions were 7.2–45, 2.8–24, 0.3–0.8, and 1.6–4.7 g kg −1 in the fresh particles from the straws burning, and 12–63, 3.0–25, 0.3–1.3, and 4.1–13 g kg −1 in the aged ones. Cl − and K + were the most abundant ions in the fresh samples. EFs of NO3 − and NH4 + were increased by 35–100 and 1.6–126 times, respectively, becoming the most abundant ions in the aged particles. By comparison with the results in experiments on 2-day aged specimens, we found a continuous formation of secondary aerosols in the atmospheric aging processes (especially for secondary inorganic ions), and that the deficit of anion equivalents increases with longer aging time. These results are valuable for studying the transportation effects of plumes from wildfires of forest and agriculture, or intensive domestic BB in some rural regions. Graphical abstract: Image 1 Highlights: PM2.5, OC, EC, and inorganic ions in fresh and 7-day aged BB aerosols were analyzed. Emission factors of PM2.5 and inorganic ions increased obviously in aging processes. Fresh Cl − could be replaced by NO3 − and/or SO4 2− in aging processes. Deficit of anion equivalents increases with longer aging time.